Draft Genome Sequence of the Biowarfare Simulant Bacillus atrophaeus Strain 930029 - Eng, Catherine (Genome Announc, 2015)
We report here the draft genome sequence of Bacillus atrophaeus strain 930029. Strain 930029 shows evidence of drift, based on a comparison to the corresponding source strain publicly available today.